1995
DOI: 10.1038/375054a0
|View full text |Cite
|
Sign up to set email alerts
|

Use of implicit motor imagery for visual shape discrimination as revealed by PET

Abstract: Positron emission tomography (PET) can be used to map brain regions that are active when a visual object (for example, a hand) is discriminated from its mirror form. Chronometric studies suggest that viewers 'solve' this visual shape task by mentally modelling it as a reaching task, implicitly moving their left hand into the orientation of any left-hand stimulus (and conversely for a right-hand stimulus). Here we describe an experiment in which visual and somatic processing are dissociated by presenting right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
355
0
7

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 629 publications
(400 citation statements)
references
References 17 publications
31
355
0
7
Order By: Relevance
“…Moreover, the fact that SMA is activated during task responding while more rostral mesial areas are recruited during task processing strengthens Wexler's thesis that mental rotation recruits motor planning and anticipation, but not the cortical and subcortical mechanisms responsible for movement execution (Wexler et al, 1998). It has been speculated that M1 activity, during mental rotation of figures of hands, was caused by the subjects visualizing themselves manipulating their right hands (Parsons et al, 1995;Kosslyn et al, 1998). Due to the stimuli used in our study, we cannot rule out that M1 might be involved in spatial processing of hand-like drawings.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, the fact that SMA is activated during task responding while more rostral mesial areas are recruited during task processing strengthens Wexler's thesis that mental rotation recruits motor planning and anticipation, but not the cortical and subcortical mechanisms responsible for movement execution (Wexler et al, 1998). It has been speculated that M1 activity, during mental rotation of figures of hands, was caused by the subjects visualizing themselves manipulating their right hands (Parsons et al, 1995;Kosslyn et al, 1998). Due to the stimuli used in our study, we cannot rule out that M1 might be involved in spatial processing of hand-like drawings.…”
Section: Discussionmentioning
confidence: 81%
“…These regions have been involved in a number of studies in motor imagery (see reviews from Grèzes and Decety, 2001;Munzert et al, 2009). Several studies using neuroimaging (Kosslyn et al, 2001), transcranial magnetic stimulation (Ganis et al, 2000), or clinical investigations (Sirigu et al, 1996) showed that motor imagery shares neural mechanisms with movement planning (Decety et al, 1989) and movement execution (Gerardin et al, 2000;Parsons et al, 1995), in particular in premotor cortex (e.g. Ionta et al, 2010) and parietal cortex (e.g.…”
Section: Shared Spectral and Anatomical Mechanisms Between Motor Imagmentioning
confidence: 99%
“…First, many brain-imaging studies of mental image transformation report activation of motor and visuomotor areas, in particular posterior parietal cortex and motor and premotor cortex. For example, Parsons et al (1995) used positron emission tomography (PET) to study mental rotation of hands. They found activation of supplementary motor cortex and the superior premotor areas, as well as motor-related parietal regions.…”
Section: Mental Image Transformation and Motor Actionmentioning
confidence: 99%